2011
DOI: 10.1073/pnas.1017234108
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies pheromone signaling promotes biofilm formation and same-sex mating in Candida albicans

Abstract: The opportunistic pathogen Candida albicans undergoes a parasexual mating cycle in which cells must switch from the conventional "white" form to the alternative "opaque" form to become mating competent. Pheromones secreted by opaque cells induce the formation of polarized mating projections and result in cell-cell conjugation. In contrast, white cells are unable to undergo mating, but can still respond to pheromone by expression of adhesion genes that promote biofilm formation. In this study, we have analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 49 publications
2
59
0
Order By: Relevance
“…5C). Our observations are supported by very recent reports that ␣-factor from C. parapsilosis (and other Candida species) induces same-sex mating and adherence in C. albicans (2).…”
Section: Analysis Of the Mating Signal Transduction Pathway In Csupporting
confidence: 90%
“…5C). Our observations are supported by very recent reports that ␣-factor from C. parapsilosis (and other Candida species) induces same-sex mating and adherence in C. albicans (2).…”
Section: Analysis Of the Mating Signal Transduction Pathway In Csupporting
confidence: 90%
“…Transformation of a self-sterile relative with the N. africana mat A sequence does not confer self-fertility seen in N. africana (GLASS and SMITH 1994 (ALBY and BENNETT 2011;GLASS and SMITH 1994;LIN et al 2005), may have evolved as a mechanism allowing species to preserve sexual reproduction and its benefits while at the same time minimising the costs (ROACH et al 2014). The cost of locating an opposite mating partner is a major barrier to efficient sexual reproduction in heterothallic fungi.…”
Section: Discussionmentioning
confidence: 99%
“…These include primary homothallism (LIN and HEITMAN 2007), as exhibited by Sodaria macrospora where both MAT idiomorph genes are present in a single genome (PÖGGELER et al 1997); mating type switching, found in S. cerevisiae where the MAT locus identity can change via gene conversion (HABER 1998) and pseudohomothallism, such as that occurring in N. tetrasperma where nuclei of opposite mating types are packaged in a single ascospore (MERINO et al 1996). A unique sub-class of homothallism known as unisexual reproduction has also been discovered in fungi, including four Neurospora spp., Cryptococcus neoformans and Candida albicans (ALBY and BENNETT 2011;GLASS and SMITH 1994;LIN et al 2005). In unisexual reproduction, also known as same-sex mating, isolates with only a single mating type have the ability to initiate and proceed through an entire sexual cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is widely accepted that the presence of both idiomorphs is necessary for sexual reproduction, fungal mating strategies are diverse and many exceptions to this rule have been observed (Heitman, 2015). For example, some species are self-fertile despite only possessing one MAT1 idiomorph (unisexual reproduction; Alby and Bennett, 2011;Glass and Smith, 1994;Lin et al, 2005;Wilson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%